Population genetics of the naked mole-rat Heterocephalus glaber: The role of rivers in shaping genetic structure - Hess, Jon; Braude, Stan; Ingram, Colleen; Templeton, Alan (Frontiers in Ecology and Evolution, 2022)
We use nested clade analysis of mitochondrial DNA sequence data to examine the processes contributing to population structure in naked mole-rats. We examined sequence variation in the (1097bp) control region D-loop of the mitochondrial genome in 303 individuals from 174 colonies of naked mole-rats Heterocephalus glaber (NMR) located mainly within an 870 km2 area in Meru National Park, Kenya. Four rivers were found to be correlated to a significant fragmentation inference in the NCPA. The largest pairwise divergence between haplotypes from populations separated by rivers was 2.74%, which was well over half of the divergence reported between the extremes of the distribution,from southern Ethiopia to southern Kenya (4.6%). However the size of the river (measured in current discharge) was not a good predictor of the amount of sequence divergence between populations separated by a river. It appears that a large-scale historical fragmentation event may have conflated fragmentation patterns on a smaller scale, when recent colonization and range expansion brought two old lineages together at a location with a relatively small river separating them.